The Practice of Exogamous Marriage from the Perspective of the Indonesian Islamic Da'wah Institution In Wonogiri Regency - Syahla Riksa Abdi Permana; Muhammad Rosyid Ridho (Faculty of Shariah UIN Ponorogo, 2025)
This study aims to explore LDII's views on exogamy or marriage with individuals outside the community. The problem that arises is that people outside LDII believe that marriage between LDII members and people outside the organization is not valid. This study employs a qualitative empirical method with a phenomenological approach to analyze the phenomenon of exogamous marriage within the LDII community. Field data collection was conducted through interviews and participatory observation involving LDII leaders, LDII officials, and members who practice exogamous marriage. The results of the study indicate that although LDII tends to support exogamous marriage, there is flexibility that allows for exogamous practices if they are considered to bring social benefits and strengthen solidarity between communities. LDII views exogamy as part of its efforts to create social harmony and maintain diversity within a broader society, without neglecting the internal values that have been built within their community. This study contributes to efforts to deconstruct social stigma toward the LDII community regarding exogamous marriage practices, while providing a more contextual understanding of the organization's stance on social pluralism. These findings also enrich academic discourse on intergroup marriage within Islamic religious organizations in Indonesia and provide an empirical foundation for the development of more inclusive social and intercommunity policies.